Metafora Perempuan Sasak dalam Novel Jatiswara Karya Lalu Agus Fathurrahman - Marlina Marlina; Saharudin Saharudin; Aswandikari Aswandikari (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Literary works not only function as aesthetic expressions, but also as a reflection of culture and social value-forming media, including representing women. Jatiswara's novel was chosen as the object of study, because it displays the symbolism of women that is full of meaning and firmly rooted in the context of Sasak culture. The purpose of this research is to describe the forms of women's metaphors and uncover the representation of Sasak women's feminism in the text of the novel. The research uses a qualitative method with the conceptual metaphor approach of Lakoff and Johnson and the concept of true women and new women feminism. The results of the study show that the metaphor of women in this novel is classified into three main categories of women's metaphors, namely structural, ontological, and orientational. The representation of Sasak women's feminism shows ambivalence, namely women present as noble true women and moral guardians, as well as new women who are critical, independent, and progressive. This research contributes to the development of the study of conceptual metaphors and local feminism in Indonesian literature.